The intelligent imitator : towards an exemplary theory of behavioral choice - Kvadsheim, Reidar, 1944-; ScienceDirect eBooks (Amsterdam ; New York : North-Holland, 1992)
This monograph presents a novel conceptual framework for the study of human social behavior with potentially far-reaching implications. Owing to the role it accords to stored memory representations of observed occurrences of actions, the proposed framework is referred to as the Exemplar Choice Theory, or "ECT". The theory links perception and action and combines an expectancy-value perspective on choice behavior, with features of recent exemplar-based approaches to the study of human information processing. It addresses the influence of social models, as well as the impact of past action consequences and differs from extant theories of instrumental learning. The volume focuses on two extreme classes of conditions defined in terms of the actor's limited access to information and discusses available evidence from many areas of psychology. Its structure is as follows: the introductory chapter locates the proposed theory within a historical context; this is followed by an overview of the main structure of the conceptual framework; subsequently, general propositions are presented and discussed in detail; later, empirical implications are derived for certain extreme classes of choice conditions and considered in the light of empirical evidence. It is hoped the publication will inspire students and researchers of psychology, biology, zoology and of many social sciences, including sociology, anthropology, decision research, marketing, economics, cognitive science and mass media studies to undertake further research and to reconsider existing data and frameworks.
Introduction -- General Overview of the Model -- Principles of Acquisition and Application of Information -- Behavior under "Minimal Conditions" -- Behavior in a "Restricted Context": Theory and Test Conditions -- How Does "Direct" Observation of Actions Affect the Observer.
Includes bibliographical references (pages 327-347) and indexes.
Print version record.
Elsevier
Keywords: Imitation; Influence (Psychology); Choice (Psychology); SELF-HELP -- Motivational & Inspirational; Choice (Psychology); Imitation; Influence (Psychology); Adaptation, Psychological; Choice Behavior; Imitative Behavior; Social Behavior; Decision making; Electronic books